Noninvasive peripheral vagal nerve stimulation prevents migraine aura: A case report - Roberto De Icco; Vito Bitetto; Daniele Martinelli; Marta Allena; Elena Guaschino; Sara Bottiroli; Eric Liebler; Cristina Tassorelli; Grazia Sances (SAGE Publishing, 2019)
We describe a patient affected by migraine with visual and somatosensory aura, whose symptoms were consistently attenuated by noninvasive peripheral vagal nerve stimulation (nVNS) in multiple prospectively recorded attacks. When compared with the current standard of care, nVNS significantly reduced the duration of visual aura in all the attacks ( n = 5) and prevented the somatosensory aura in three of the five attacks. The overall duration of nVNS-treated auras was 19.0 ± 4.2 min, significantly shorter than the duration of aura in attacks treated with standard of care (103.8 ± 10.3 min). This single-case study requires confirmation in a larger sample size, but we believe that this first report is suggestive of likely efficacy given the relatively high number of treated attacks and the consistent effect of nVNS.